-
Notifications
You must be signed in to change notification settings - Fork 0
/
math.tex
232 lines (211 loc) · 11.8 KB
/
math.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
\section{Mathematical Background}
% \begin{theorem}[Concentration of Gamma]
% Consider a family $\{ X_i \}_{i \in [n]}$ of i.i.d. random variables $X_i$ distributed as $\Exp(\lambda)$, $\lambda > 0$,
% and let $X = \sum_{i = 1}^{n}{X_i}$. Then, for any $0 < \epsilon < 1$, it holds that
% $\Pr[X > (1 + \epsilon) \E[X]] < e^{-n(\epsilon - \ln(1 + \epsilon))}$,
% which is negligible in $n$.
% \end{theorem}
% \begin{proof}
% % First, we calculate the expectation:
% %
% % \[
% % \E[X] = \E[\sum_{i = 1}^n X_i] = \sum_{i = 1}^n \E[X_i] = n \E[X_i] = \frac{n}{\lambda}
% % \]
% %
% % Next, we calculate the moment generating function:
% %
% % \[
% % \E[e^{tX}] = \E[e^{t \sum_{i = 1}^n} X_i] = \E[\prod_{i = 1}^n e^{t X_i}] = \prod_{i = 1}^n \E[e^{t X_i}]
% % = \E[e^{t X_i}]^n = (\frac{\lambda}{\lambda - t})^n
% % \]
% %
% % The third equality stems from the mutual independence of the family $\{ X_i \}_{i \in [n]}$,
% % whereas the last equality stems from the moment generating function of the exponential.
% $X$ is distributed as $\Gamma(\alpha=n, \beta=\lambda)$. Therefore
% $\E[X] = \frac{n}{\lambda}$ and the moment generating
% function is $\E[e^{tX}] = (\frac{\lambda}{\lambda - t})^n = e^{n\ln(\frac{\lambda}{\lambda - t})}$.
%
% % For all $0 < t < \lambda$,
% % \begin{align*}
% % \Pr[X > \alpha] = \Pr[e^{tX} > e^{t\alpha}] \leq \frac{\E[e^{tX}]}{e^{t\alpha}}\,.
% % \end{align*}
%
% % The first equality is by the fact that the exponential function is increasing,
% % whereas the second inequality is Markov's inequality.
% \begin{align*}
% \Pr[X > (1 + \epsilon)\E[X]] = \Pr[X > (1 + \epsilon)\frac{n}{\lambda}] \leq \E[e^{tX}] e^{-t(1 + \epsilon)\frac{n}{\lambda}}\\
% = e^{n\ln(\frac{\lambda}{\lambda - t}) - t(1 + \epsilon)\frac{n}{\lambda}}\,.
% \end{align*}
%
% The first inequality is by the generic Chernoff bound.
% To minimize the exponent over $t$, we differentiate it and equate to $0$:
%
% \begin{align*}
% \frac{d}{dt}(\ln(\frac{\lambda}{\lambda - t}) - t(1 + \epsilon)\frac{1}{\lambda}) &= 0\\
% \frac{d}{dt}{\ln\lambda - \ln(\lambda - t) - t(1 + \epsilon)\frac{1}{\lambda}} &= 0\\
% \frac{1}{\lambda - t} - (1 + \epsilon)\frac{1}{\lambda} &= 0\\
% \frac{1}{\lambda - t} &= (1 + \epsilon)\frac{1}{\lambda}\\
% \lambda - t &= \frac{\lambda}{1 + \epsilon}\\
% t &= \lambda(1 - \frac{1}{1 + \epsilon}) = \frac{\lambda \epsilon}{1 + \epsilon}\,.
% \end{align*}
%
% We substitute $t$ in the exponent:
%
% \begin{align*}
% n \ln(\frac{\lambda}{\lambda - t}) - t(1 + \epsilon)\frac{n}{\lambda} = \\
% n \ln(\frac{\lambda}{\lambda - \frac{\lambda\epsilon}{1 + \epsilon}}) - \frac{\lambda \epsilon}{1 + \epsilon}(1 + \epsilon)\frac{n}{\lambda} = \\
% n \ln(\frac{1}{1 - \frac{\epsilon}{1 + \epsilon}}) - \epsilon n = \\
% n \ln(\frac{1}{\frac{1 + \epsilon - \epsilon}{1 + \epsilon}}) - \epsilon n = \\
% n \ln(1 + \epsilon) - \epsilon n = \\
% -n (\epsilon - \ln(1 + \epsilon))\\
% \end{align*}
%
% The exponent is negative because
% \begin{align*}
% \epsilon - \ln(1 + \epsilon) > 0 \Leftrightarrow \\
% \epsilon > \ln(1 + \epsilon)\\
% e^{\epsilon} > 1 + \epsilon\,,
% \end{align*}
% which holds because $\epsilon > 0$.
% \end{proof}
\begin{lemma} \label{lem:bernoulli}
For all $0 < y < 1$, it holds that $2^y - 1 < y$
and $1 - 2^{-y} < y$.
\end{lemma}
\begin{proof}
For the first part,
it suffices to show that $(y + 1)^{1/y} > 2$,
as this implies that $2^y < y + 1$ and, ultimately, $2^y - 1 < y$.
The inequality $(y + 1)^{1/y} > 2$ holds due to Bernoulli's
inequality ($(1 + x)^r > 1 + rx$ for all $x > 0$ and $r > 1$),
when setting $x = y$ and $r = \frac{1}{y}$.
For the second part,
it suffices to show that $(1 - y)^{1/y} < \frac{1}{2}$.
Let $f(y) = (1 - y)^{1/y}$ and
\begin{align*}
\frac{d}{dy} f(y) = \frac{d}{dy} (1 - y)^{1/y} = \frac{d}{dy} e^{\frac{1}{y}\ln(1 - y)} =\\
(1 - y)^{1/y} \left(-\frac{1}{y (1 - y)} - \frac{\ln(1 - y)}{y^2}\right) =\\
(1 - y)^{1/y} \left(\frac{y - (y - 1) \ln(1 - y)}{y^2(y - 1)}\right)
\end{align*}
Letting $\phi(y) = y - (y - 1) \ln(1 - y)$, we have
$\frac{d}{dy} f(y) = (1 - y)^{1/y} \left(\frac{\phi(y)}{y^2(y - 1)}\right)$.
Observe that $\phi(y)$ is continuous and differentiable for $y \in (0, 1)$.
It holds that
\begin{align*}
\frac{d}{dy} \phi(y) = \frac{d}{dy} (y - (y - 1) \ln(1 - y)) =\\
\frac{d}{dy} (y - y \ln(1 - y) + \ln(1 - y)) =\\
1 - \ln(1 - y) + \frac{y}{1 - y} - \frac{1}{1 - y} =\\
1 - \ln(1 - y) - \frac{1 - y}{1 - y} = -\ln(1 - y)
\end{align*}
Hence, for $y \in (0, 1)$, it holds that $\frac{d}{dy} \phi(y) > 0$ and
$\phi(y)$ is increasing. Because $\phi(0) = 0$,
it holds that $\phi(y) > 0$ for $y \in (0, 1)$.
Therefore, for $y \in (0, 1)$, it holds that $\frac{d}{dy} f(y) < 0$
and $f(y)$ is decreasing.
Setting $\omega = - \frac{1}{y}$, we have
\begin{align*}
\lim_{y \to 0}f(y) = \lim_{y \to 0}(1 - y)^{\frac{1}{y}} = \lim_{\omega \to -\infty}\left(1 + \frac{1}{\omega}\right)^{-\omega} =\\
\frac{1}{\lim_{\omega \to -\infty}\left(1 + \frac{1}{\omega}\right)^{\omega}} = \frac{1}{e}
\end{align*}
Pick an arbitrary $0 < \epsilon < \frac{1}{2} - \frac{1}{e}$. By the definition of the limit,
there exists a $\delta > 0$ such that for all $y \in (0, \delta)$, it holds that
$|f(y) - \frac{1}{e}| < \epsilon \Leftrightarrow f(y) < \frac{1}{2}$.
Hence, for $y \in (0, 1)$, because $f(y)$ is continuous and decreasing, it holds that
$f(y) < \frac{1}{2}$.
\Qed
\end{proof}
\begin{lemma}[Concentration of $\Bern \times \Exp$]\label{lem:bern-exp}
Let $\{ A_i \}_{i \in [n]}$ and $\{ B_i \}_{i \in [n]}$ be two families of i.i.d. random variables,
all mutually independent,
with $A_i$ distributed as $\Bern(p)$ and $B_i$ distributed as $\gamma + \Exp(\lambda)$,
the exponential distribution shifted by a constant $\gamma \geq 0$.
Let $X_i = A_i B_i$, and $X = \sum_{i = 1}^n X_i$.
Then for any $0 < \epsilon < 1$, it holds that
$\Pr[X > (1 + \epsilon) \E[X]] < e^{-\Omega(n)}$ and
$\Pr[X < (1 - \epsilon) \E[X]] < e^{-\Omega(n)}$,
which is negligible in $n$.
\end{lemma}
\begin{proof}
$\E[X_i] = \E[A_i B_i] = \E[A_i] \E[B_i] = p(\gamma + \frac{1}{\lambda})$, therefore
$\E[X] = np(\gamma + \frac{1}{\lambda})$. For the moment generating functions we have
\begin{align*}
&\E[e^{t X_i}] = \E[e^{t A_i B_i}] =\\
&\E[e^{t A_i B_i}|A_i = 0] \Pr[A_i = 0]\\
+ &\E[e^{t A_i B_i}|A_i = 1] \Pr[A_i = 1] = \\
\E[e^{t A_i B_i}|A_i = 0] (1 - p) + &\E[e^{t A_i B_i}|A_i = 1] p = \\
(1 - p) + p \E[e^{t B_i}] &= (1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\,.
\end{align*}
\begin{align*}
\E[e^{tX}] = \E[e^{t \sum_{i = 1}^n X_i}] = \E[\prod_{i = 1}^n e^{t X_i}] = \prod_{i = 1}^n \E[e^{t X_i}] = \\
\E[e^{t A_i B_i}]^n = \left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right]^n =
e^{n \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right]}\,.
\end{align*}
For all $0 < t < \lambda$:
\begin{align*}
\Pr[X > (1 + \epsilon)\E[X]] = \Pr[X > (1 + \epsilon)np(\gamma + \frac{1}{\lambda})] =
\Pr[e^{tX} > e^{t(1 + \epsilon)np(\gamma + \frac{1}{\lambda})}]\\
\leq \E[e^{tX}] e^{-t(1 + \epsilon)np(\gamma + \frac{1}{\lambda})}
= e^{n \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - nt(1 + \epsilon)p(\gamma + \frac{1}{\lambda})}\,.
\end{align*}
Consider the factor
$f(t) = \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - t(1 + \epsilon)p(\gamma + \frac{1}{\lambda})$
in front of $n$ in the exponent. Taking its derivative with respect to $t$:
\begin{align*}
\frac{d}{dt} \left(\ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - t(1 + \epsilon)p\left(\gamma + \frac{1}{\lambda}\right)\right) = \\
\frac{1}{(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}} \frac{d}{dt} \left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - (1 + \epsilon)p\left(\gamma + \frac{1}{\lambda}\right) = \\
\frac{pe^{t\gamma}\frac{\lambda}{\lambda - t}(\gamma + \frac{1}{\lambda - t})}{(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}} - (1 + \epsilon)p\left(\gamma + \frac{1}{\lambda}\right)
\end{align*}
At $t = 0$ we have $f(0) = 0$ and
\begin{align*}
\frac{d}{dt} f(0) = \frac{p(\gamma + \frac{1}{\lambda})}{1 - p + p} - (1 + \epsilon)p\left(\gamma + \frac{1}{\lambda}\right) =\\
p \left(\gamma + \frac{1}{\lambda}\right) - (1 + \epsilon)p \left(\gamma + \frac{1}{\lambda}\right) = -\epsilon p \left(\gamma + \frac{1}{\lambda}\right) < 0\,.
\end{align*}
Since $\frac{d}{dt} f$ is continuous at $0$ and $\frac{d}{dt} f(0) < 0$, there must exist some $0 < t^* < \lambda$ such that for all
$0 < t < t^*$ it holds that $\frac{d}{dt} f(t) < 0$. Because $f$ is continuous and differentiable in $[0, t^*]$,
by the Mean Value Theorem, there must exist some $\xi \in (0, t^*)$ such that
$\frac{d}{dt} f(\xi) = \frac{f(t^*) - f(0)}{t^* - 0} = \frac{f(t^*)}{t^*}$.
Since $t^* > 0$ and $\frac{d}{dt} f(\xi) < 0$, therefore $f(t^*) < 0$.
This $t^*$ makes the factor in front of $n$ in the exponent negative, and therefore
gives us a bound for which $\Pr[X > (1 + \epsilon)\E[X]] < e^{-\Omega(n)}$.
For all $t < 0$:
\begin{align*}
\Pr[X < (1 - \epsilon)\E[X]] = \Pr\left[X < (1 - \epsilon)np(\gamma + \frac{1}{\lambda})\right] = \Pr[e^{tX} > e^{t(1 - \epsilon)np(\gamma + \frac{1}{\lambda})}]\\
% \leq \E[e^{tX}] e^{-t(1 - \epsilon)\frac{np}{\lambda}} \\
\leq \E[e^{tX}] e^{-t(1 - \epsilon)np(\gamma + \frac{1}{\lambda})} \\
= e^{n \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - t(1 - \epsilon)np(\gamma + \frac{1}{\lambda})}
\end{align*}
Consider the factor
$f(t) = \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - t(1 - \epsilon)p(\gamma + \frac{1}{\lambda})$
in front of $n$ in the exponent. Taking its derivative with respect to $t$:
\begin{align*}
\frac{d}{dt} \left( \ln\left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - t(1 - \epsilon)p(\gamma + \frac{1}{\lambda}) \right) = \\
\frac{1}{(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}} \frac{d}{dt} \left[(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}\right] - (1 - \epsilon)p(\gamma + \frac{1}{\lambda}) = \\
\frac{pe^{t\gamma}\frac{\lambda}{\lambda - t}(\gamma + \frac{1}{\lambda - t})}{(1 - p) + pe^{t\gamma}\frac{\lambda}{\lambda - t}} - (1 - \epsilon)p(\gamma + \frac{1}{\lambda})
\end{align*}
At $t = 0$ we have $f(0) = 0$ and
\begin{align*}
\frac{d}{dt} f(0) = \frac{p(\gamma + \frac{1}{\lambda})}{(1 - p) + p} - (1 - \epsilon)p(\gamma + \frac{1}{\lambda}) =\\
p (\gamma + \frac{1}{\lambda}) - (1 - \epsilon)p (\gamma + \frac{1}{\lambda}) = \epsilon p (\gamma + \frac{1}{\lambda}) > 0\,.
\end{align*}
Since $\frac{d}{dt} f$ is continuous at $0$ and $\frac{d}{dt} f(0)> 0$, there must exist some $t^* < 0$ such that for all
$t^* < t < 0$ it holds that $\frac{d}{dt} f(t) > 0$. Because $f$ is continuous and differentiable in $[t^*, 0]$,
by the Mean Value Theorem, there must exist some $\xi \in (t^*, 0)$ such that
$\frac{d}{dt} f(\xi) = \frac{f(0) - f(t^*)}{0 - t^*} = \frac{f(t^*)}{t^*}$.
Since $t^* < 0$ and $\frac{d}{dt} f(\xi) > 0$, therefore $f(t^*) < 0$.
This $t^*$ makes the factor in front of $n$ in the exponent negative, and therefore
gives us a bound for which $\Pr[X < (1 - \epsilon)\E[X]] < e^{-\Omega(n)}$.
\Qed
\end{proof}
% \begin{lemma}
% $f(\kappa) = 2^{\frac{nqL + 1}{2^{\kappa/2}}} - 1$ is negligible.
% \end{lemma}
% \begin{proof}
% It suffices to show that $f(\kappa) < \frac{nqL + 1}{2^{\kappa/2}}$
% for sufficiently large $\kappa$, since $\frac{nqL + 1}{2^{\kappa/2}}$
% is negligible.
% This follows by applying Lemma~\ref{lem:bernoulli} for $y = \frac{nqL + 1}{2^{\kappa/2}}$.
% Note that, for large enough $\kappa$, the exponent $\frac{nqL + 1}{2^{\kappa/2}}$
% falls within the range $0 < \frac{nqL + 1}{2^{\kappa/2}} < 1$,
% so the lemma is applicable.
% \Qed
% \end{proof}